SAYLAW HUQÍQÍ – PUQARALARDÍŃ SIYASIY HUQÍQÍ SÍPATÍNDA - Tilewov, E.M.; Pirniyazova, M.K. (SCIENCE and SOCIETY, 2022)
The article discusses the electoral rights of citizens, culture and democracy, the principles of holding elections and their implementation, as well as the responsibility established by the law of the Republic of Uzbekistan for violations of electoral norms.
Keywords: coutry; society; personality; constitution; code; democracy; referendum; active election; passive election; regulatory document